Gap detection within and across auditory channels in younger and older listeners - Heinrich, Antje; Schneider, Bruce A. (Canadian Acoustics, 2002)
Young and old adult listeners were tested in within and between channel gap detection tasks using pure tones of two different center frequencies. The aging auditory system was characterized by accumulating deficits particularly in peripheral processes. The results found larger and more variable gap thresholds for older normal hearing listeners in within channel comparisons.